Subclinical left ventricular dysfunction and correlation with regional strain analysis in myocarditis with normal ejection fraction. A new diagnostic criterion. (15th May 2018) - Kostakou, Peggy M.; Kostopoulos, Vassilis S.; Tryfou, Elsi S.; Giannaris, Vassilis D.; Rodis, Ioannis E.; Olympios, Christoforos D.; Kouris, Nikos T.
Abstract: Background: The diagnosis of myocarditis is challenging, especially in case of normal left ventricular systolic function. The aim of this study is to test the hypothesis that 2D speckle tracking echocardiography (2DSTE) can detect subclinical left ventricular (LV) dysfunction in patients with myocarditis and preserved LV function without regional wall motion abnormalities and that regional strain analysis can correlate with cardiac magnetic resonance (CMR) findings. Methods: Study population consisted of 25 consecutive patients with myocarditis and 19 controls. All patients underwent a full echocardiographic study at the first day of their admission and in addition to conventional echocardiographic measurements, global longitudinal and circumferential strain of the left ventricle (LVGLS, LVCS accordingly), as well as regional strains of the lateral wall, were estimated. Moreover, all patients underwent a CMR scan during the first week from their admission. Results: Although there was no statistical difference between the two groups of patients in systolic function, myocarditis patients demonstrated significantly impaired LVGLS (−16.5 ± 2.2 vs −20.5 ± 1.3%, p < 0.0001) and LVCS (−16.4 ± 3.7 vs −20.9 ± 2%, p = 0.002), as well as segmental longitudinal strains of the lateral wall. CMR in all myocarditis patients revealed late gadolinium enhancement in the lateral left ventricle free wall. Conclusions: In patients with acute myocarditis with preserved ejection fraction, 2DSTE evaluation appears to be a promising, useful noninvasive and inexpensive tool in addition to existing methods used for the diagnosis of acute myocarditis, since it seems to be able to identify myocardial fibrosis early in the setting of the disease. Graphical abstract: Histological evidence of inflammatory infiltration within the myocardium associated with myocyte degeneration corresponding to reduced lateral wall strain as it is represented by speckle tracking echocardiography (Bull's eye). The same finding is confirmed by cardiac magnetic resonance with the late gadolinium enhancement in the lateral left ventricle free wall. Highlights: A noninvasive and inexpensive tool for acute myocarditis diagnosis is proposed. The patients had no wall motion abnormality and preserved ejection fraction. The diagnosis is relied on impaired left ventricle lateral wall strain. This finding is in accordance with cardiac magnetic resonance findings.